KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN BONTOBAHARI KABUPATEN BULUKUMBA - Nurhalisa, Nurhalisa; Hakim, Lukman; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2025)
This research aims to determine the quality of public services at the Bontobahari sub-district office, Bulukuma district. This research uses qualitative methods with a descriptive type. Data collection techniques include observation, interviews and documentation. Data validation includes source triangulation. The results of this research show that the quality of public services at the Bontobahri District Office is direct evidence (Tangible). The results of the research show that the facilities and infrastructure such as buildings and completeness of facilities are inadequate, (Reliability) can be said to be good because by implementing monitoring and evaluation, clear communication. and following active training, the employees are very reliable in service. Responsiveness can be said to be good. This can be seen from the results of interviews with the public saying that the employees of the Bontobahari sub-district office are quite responsive to the needs of the community. Empathy (Emphaty) cannot be said to be good because there are still some employees who are not friendly towards the public.